A Proposed New Nomenclature for the Immunoglobulin Genes of Mus musculus - Busse, Christian E.; Jackson, Katherine J. L.; Watson, Corey T.; Collins, Andrew M. (Frontiers in Immunology, 2019)
Mammalian immunoglobulin (IG) genes are found in complex loci that contain hundreds of highly similar pseudogenes, functional genes and repetitive elements, which has made their investigation particularly challenging. High-throughput sequencing has provided new avenues for the investigation of these loci, and has recently been applied to study the IG genes of important inbred mouse strains, revealing unexpected differences between their IG loci. This demonstrated that the structural differences are of such magnitude that they call into question the merits of the current mouse IG gene nomenclatures. Three nomenclatures for the mouse IG heavy chain locus (Igh) are presently in use, and they are all positional nomenclatures using the C57BL/6 genome reference sequence as their template. The continued use of these nomenclatures requires that genes of other inbred strains be confidently identified as allelic variants of C57BL/6 genes, but this is clearly impossible. The unusual breeding histories of inbred mouse strains mean that, regardless of the genetics of wild mice, no single ancestral origin for the IG loci exists for laboratory mice. Here we present a general discussion of the challenges this presents for any IG nomenclature. Furthermore, we describe principles that could be followed in the formulation of a solution to these challenges. Finally, we propose a non-positional nomenclature that accords with the guidelines of the Mouse Genome Nomenclature Committee, and outline strategies that can be adopted to meet the nomenclature challenges if three systems are to give way to a new one.